Penegakan Hukum Terhadap Korupsi Di Indonesia: Antara Upaya, Kendala Politik, Dan Integritas Aparat - Kaysa Alifia Mecca; Fanisa Nuraziza; Ribi Aulia (JUSTNESS - Jurnal Hukun Politik dan Agama, 2025)
Corruption is a crucial threat because it can hinder development, damage the political and economic order and harm justice in Indonesia. This study uses a literature study method, by reviewing various secondary sources such as scientific journals, books, and laws and regulations that are relevant to the topic discussed. The results of this discussion are that Corruption is an act that is not commendable or a crime that is very detrimental to others by taking or seizing the rights of others that should be received by the person himself. Corruption not only harms the state in terms of finances, but can also increase public trust in the law and law enforcement officers. Law Number 3 of 1971 is an important step to expand and expand the definition of criminal acts of corruption, which later became Law Number 31 of 1999 as the main basis for eradicating corruption in Indonesia. There are three strategies for handling criminal acts of corruption in Indonesia in the Trident of corruption eradication, which consists of action, prevention and education. but all of that is inseparable from the obstacles that always exist such as political intervention and the weak integrity of law enforcement officers. In addition to the existing obstacles, various efforts have been made, such as the formation of the Corruption Eradication Committee (KPK) and increasing public awareness